Analysis of Sales Distribution Strategy Gallon Water at Harmoni Water Using Monte Carlo Method - Yusniwati Tafonao; Hasanul Fahmi (Institute of Computer Science (IOCS), 2020)
Distribution problems currently have an important role in the distribution of goods from producers to consumers because the main function of distribution is the distribution of goods. Currently, Harmoni Water has problems in distribution, the large demand for gallon water causes Harmoni Water to experience problems in distributing water to consumers, so the problems that occur cause Harmoni Water to need a method that is able to find the shortest route for water distribution. so that to solve the problem in Harmoni Water, a monte carlo method is needed to generate random random numbers which can determine the shortest path in the distribution of gallon water in Harmoni Water.